Mothers' and fathers' experiences of breastfeeding and returning to paid work after birth: A mixed‐method study - Jennifer Ayton; Sue Pearson; Alison Graham; Gemma Kitsos; Emily Hansen (Maternal and Child Nutrition)
Abstract This mixed‐method study explored the experiences of mothers and fathers combining breastfeeding with returning to paid employment after childbirth. Tasmanian State Service employees participated in an online survey and phone interviews. A total of 130 parents completed the survey, and 42 participated in 60‐min phone interviews. The survey had more female respondents (109) than male (21), and only 4 of the 42 interviews were with fathers. The sample consisted mainly of professional women (84%) and men (16%), predominantly Australian‐born (88%). Two‐thirds of participants worked part‐time (62%), taking either unpaid (52%) or paid leave (61%) within the first 12 months after birth. The majority (88%) preferred to breastfeed, with the mean age of the first formula feed being 4.1 months. A narrative analysis of the qualitative data, informed by work–family conflict theory, reveals that transitioning back to paid work while breastfeeding is challenging for both mothers and fathers. Parents face multiple conflicts between paid work, family responsibilities and maintaining breastfeeding. The emotional and physical demands of feeding, expressing, storing and transporting breast milk, combined with often inadequate workplace facilities, policies and gender discrimination, add to parental pressure. Mothers bear the greatest burden, while fathers’ roles and needs are often overlooked in the workplace. The major finding of this study is that breastfeeding is insufficiently recognised as an integral part of the return‐to‐work process for both parents, generating a form of work–family breastfeeding conflict, where work (part‐time or full‐time) interferes with family responsibilities and breastfeeding. Family‐friendly breastfeeding policies based on equity principles are needed to address workplace gender inequality and discrimination and better support parents in combining work and breastfeeding.